Relation of Steroid on Linear Growth Velocity with Biochemical Bone Markers in Children with Nephrotic Syndrome in a Teaching Hospital, Central Nepal - Pan, Atanu; Jana, Debarshi (Journal of College of Medical Sciences-Nepal, 2020)
Background: Nephrotic Syndrome is the clinical manifestation of glomerular diseases associated with heavy (nephrotic range) proteinuria. This study was done to compare biochemical bone markers in nephrotic children on steroid therapy and the linear growth velocity in children with nephrotic syndrome receiving steroid with that of known available reference standard for children of same age and sex groups Methods: A hospital based comparative study was conducted in the Department of Pediatrics, College Of Medical Sciences, Bharatpur, Nepal among 40 Study group and 40 Comparatvie group by taking the data from 2014 to 2018. Results: We found that in study group, the Mean Vitamin D of patients was 12.6293 ± 3.4974 which was low. Present study found that in Study group, the Mean serum Ca (Mean± SD.) of patients was 6.8000 ± .9672. In comparative group, the Mean serum Ca (Mean± SD.) of patients was 9.6907 ± .9218. Difference of Mean serum Ca vs. group was statistically significant (p<0.0001). Conclusions: We found that the Mean albumin significant lower in study group compared to comparative group but total cholesterolsignificant higher in study group. Vitamin D and calcium were low in Study group which was statistically significant.